Erratum: Layer-dependent quantum cooperation of electron and hole states in the anomalous semimetal WTe2 - Pranab Kumar Das (Nature Portfolio, 2016)
Nature Communications 7, Article number: 10847 (2016); Published 29 February 2016; Updated 13 April 2016. This Article contains errors in the numbering of the references in the text. The third sentence of the second paragraph should only refer to reference 2, not references 2 and 3. The correct sentence is: